MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA - Permatasari, Carolina Lita (Satya Widya, 2023)
The learning process of science in grade V of Marsudirini Perawang Elementary School showed unsatisfactory learning results, which was not reaching the minimum completeness criteria, so that class action research was carried out by applying Student Team Achievement Division (STAD) to improve student learning outcomes. The research was held in October 2021 in two cycles. Each cycle consisted of two meetings. The research procedure consists of planning, implementation, observation, and reflection. The research subjects were 32 students in grade V. The data collection instruments used were observation sheets. The assessment instruments used were formative test 1 and formative test 2, which were carried out at the end of each cycle. The pre-cycle score was 63.4, the average score of the first formative was 83.37, and the average score of second formative test was 86.78. The increase in student activity from the first cycle to the second cycle was 15%, and the increase in teacher’s activity was 5%. From these data, it is concluded that STAD model could improve the learning outcomes of Science at Marsudirini Perawang Elementary School grade V in the academic year 2021-2022.